2010
DOI: 10.3899/jrheum.100361
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Therapy for Systemic Sclerosis: A Systematic Review

Abstract: Anti-tumor necrosis factor-α agents may improve inflammatory arthritis and disability in SSc. The effect on skin score is uncertain. Adequately powered trials are needed to evaluate efficacy, and longitudinal studies are needed to evaluate longterm safety of these agents in SSc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 47 publications
(100 reference statements)
1
30
0
2
Order By: Relevance
“…43 Biological blockers of tumor necrosis factor (anti-TNF) were not used in our patients, although they proved to be useful and effective in the treatment of arthritis associated with inflammatory SSc. [45][46][47][48] Bosello et al suggested that the use of anti-TNF in medium-term could also be beneficial to reduce the progression of fibrotic disease and control of ulcerations, 46 but other studies did not observe any improvement in the skin score and in the pulmonary function with therapy. 45,47 Moreover, Omair et al reported malignancies (breast cancer, basal cell carcinoma and leukemia) in a third of patients receiving anti-TNF therapy 47 and now the European group of experts on the scleroderma and systemic sclerosis trials and research (EUSTAR) does not recommend the routine use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Biological blockers of tumor necrosis factor (anti-TNF) were not used in our patients, although they proved to be useful and effective in the treatment of arthritis associated with inflammatory SSc. [45][46][47][48] Bosello et al suggested that the use of anti-TNF in medium-term could also be beneficial to reduce the progression of fibrotic disease and control of ulcerations, 46 but other studies did not observe any improvement in the skin score and in the pulmonary function with therapy. 45,47 Moreover, Omair et al reported malignancies (breast cancer, basal cell carcinoma and leukemia) in a third of patients receiving anti-TNF therapy 47 and now the European group of experts on the scleroderma and systemic sclerosis trials and research (EUSTAR) does not recommend the routine use.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47][48] Bosello et al suggested that the use of anti-TNF in medium-term could also be beneficial to reduce the progression of fibrotic disease and control of ulcerations, 46 but other studies did not observe any improvement in the skin score and in the pulmonary function with therapy. 45,47 Moreover, Omair et al reported malignancies (breast cancer, basal cell carcinoma and leukemia) in a third of patients receiving anti-TNF therapy 47 and now the European group of experts on the scleroderma and systemic sclerosis trials and research (EUSTAR) does not recommend the routine use. 48 Regarding the use of other biologicals in SSc, they were not necessary in our patients with arthritis due to a good response with the use of rituximab, although the EUSTAR group concluded in an observational study that tocilizumab and abatacept appeared to be safe and effective in the treatment of refractory polyarthritis in patients with SSc, but there were no significant changes in lung or skin fibrosis in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…39 These findings have been replicated in other studies. 40,41 Of concern, 30% of patients developed a malignancy, 39 a finding that requires further investigation. Tocilizumab, an interleukin 6 receptor blocker, and abatacept, a costimulatory signal modulator, were found to be safe and efficacious in treating refractory SSc arthritis in a small observational study of 20 patients.…”
Section: Therapy For Musculoskeletal Manifestations Of Systemic Sclermentioning
confidence: 99%
“…Patients with psoriasis can achieve significant improvement with this immunotherapy. Other studies evaluated its use for aGVHD, 97 Behç et disease, 85 necrobiosis lipoidica diabectorum, 98 pityriasis rubra pilaris, 99 SAPHO syndrome, 100 scleroderma, 101 subcorneal pustular dermatosis, 102 and toxic epidermal necrolysis. 103 …”
Section: Infliximab (Remicade)mentioning
confidence: 99%